2011
DOI: 10.1007/s11906-011-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Nocturnal Blood Pressure Reduction the Secret to Reducing the Rate of Progression of Hypertensive Chronic Kidney Disease?

Abstract: Hypertension is a significant risk factor for cardiovascular and renal disease. Lowering blood pressure (BP) has been shown to reduce the incidence of cardiovascular disease, but randomized trials have not demonstrated a benefit of lowering BP for the progression of renal disease except in secondary analyses in patients with significant proteinuria. Recently, there has been increasing interest in measuring BP outside of the clinic, using both home and ambulatory blood pressure monitoring (ABPM). ABPM has the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Nighttime systolic blood pressure may be the best predictor of cardiovascular disease and mortality (2); one prior study has shown that evening dosing of a single once daily antihypertensive medication may reduce adverse cardiovascular outcomes (2,3,8,9). Hermida et al studied 2156 randomized subjects to demonstrate significant effects of administration time, specifically a lower CVD event risk (i.e., death, myocardial infarction, stroke) (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nighttime systolic blood pressure may be the best predictor of cardiovascular disease and mortality (2); one prior study has shown that evening dosing of a single once daily antihypertensive medication may reduce adverse cardiovascular outcomes (2,3,8,9). Hermida et al studied 2156 randomized subjects to demonstrate significant effects of administration time, specifically a lower CVD event risk (i.e., death, myocardial infarction, stroke) (8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous trials have demonstrated that treatment of hypertension reduces the risk for cardiovascular disease and all-cause mortality (1,2). Nearly all prior studies have investigated the effect of reduction in clinic blood pressure rather than in ambulatory blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in ambulatory blood pressure monitoring (ABPM) have demonstrated that a higher night-time BP and a nondipper BP pattern are good predictors of cardiovascular events (3,4) and progression of renal disease (5,6). Cardiovascular morbidity and mortality are also reported to elevate in hypertensive patients with a non-dipper BP pattern even under antihypertensive drugs (7).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nighttime blood may be a robust predictor of long term outcomes [5••]. This has raised increased interest in diurnal variation in BP and elevation in nocturnal BP as a prognostic and therapeutic target [4,6,7]. Chronic kidney disease (CKD) becomes particularly relevant, due to its high prevalence in populations with altered diurnal BP and its potential for target organ damage [8].…”
Section: Introductionmentioning
confidence: 99%